P-262 Engaging with our community to create a new hospice strategy. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Stevens, Alison; Bridger, Sue
Abstract : Background: Traditionally our hospice strategy was prepared by the Board of Trustees, Chief Executive and Senior Management Team. Aim: We wanted an innovative way to engage with our community to find out their ideas to help us shape a new strategic plan. Methodology: We created a strategy group made up of staff, volunteers and trustees and an idea evolved to use a Postcard campaign - 'Every Voice Matters'. We asked only one question – 'What would you like to see from the hospice in the future?' Strategy Champions donned their strategy t-shirts delivering post-cards and post boxes to key locations including GP surgeries, leisure centres, libraries and handed them out at events to ask as many people as possible to have their say. People responded by posting cards in our boxes, by freepost, email, on our website and via Facebook or Twitter. Results: Responses were collated and key themes shared with staff and volunteers for further comments on how our new strategic plan could be delivered. All information received was then used to form a new strategic plan with four key goals: Reach out; Empower; Invest; Inspire. Three detailed objectives were agreed for each strategic goal linking to an overarching organisational annual operational plan. Once our new strategy was approved by the Board an extensive community engagement plan was put in place. This provided opportunities to promote our services at high profile events where we invited people with influence from many different backgrounds, asking for their ongoing support. Further community engagement included a wide ranging public awareness campaign. Conclusion : Overall the involvement of our community in preparation and dissemination of our new strategy has proved very worthwhile. To ensure ongoing inclusion of our community in our plans a new hospice advisory group PATH (People Advising the Hospice) has been established.